Challenges for Scientists in Latin America. Issue 9 (September 2016) - Kalergis, Alexis M.; Lacerda, Marcus; Rabinovich, Gabriel A.; Rosenstein, Yvonne
Abstract : Despite political turmoil and economical crisis, research in Latin America has considerably advanced over recent decades. The present 'Point of View' outlines our perspectives on the working conditions, successes, difficulties, limitations, and challenges of biomedical scientific communities in four Latin American countries: Argentina (G.A.R.), Brazil (M.L.), Chile (A.K.), and Mexico (Y.R.).